Microstructure Analysis of Mass Variations of LiOH/Cassava Peel Activated Carbon Nanocomposite - Lidya Agraini; Darvina, Yenni (Journal of Experimental and Applied Physics, 2024)
The need for electronic devices has grown quite rapidly. To operate electronic devices, batteries are needed. The most widely used battery is a rechargeable battery type lithium ion battery. the advantages of using rechargeable batteries are practical and easy to carry everywhere. One of the disadvantages of rechargeable batteries is not able to work at high power. For this reason, it is necessary to conduct research on the forming material on the battery anode. This study was intended to characterize the structure, field and crystal size of the mass variation of LiOH/cassava peel activated carbon nanocomposite synthesized using the sol gel method with a mass variation ratio of 40%: 60%, 50% : 50%, and 60%: 40%.The LiOH/cassava peel activated carbon nanocomposite was mixed with PEG 6000 solution stirred at 100º C to form a gel which was dried and pulverized. XRD characterization was carried out and analyzed using High Score Plus software. Carbon has a cubic crystal structure with a diffraction peak of 29.41º. Activated carbon has a hexagonal crystal structure with diffraction peaks of 31.53º and 44.48º. The nanocomposite has a crystal structure that is hexagonal and orthorhombic for the carbon phase, while LiOH is monoclinic with different miller indices. The nanocomposite crystal size is 26.33 nm to 79.01 nm, with the smallest crystal size found when the LiOH/activated carbon nanocomposite variation is 40%: 60%. From the three comparisons, the more carbon the smaller the crystal size.